International tourists' attitude and intention to visit green hotels in Malaysia - Patwary, Ataul Karim (2021)
The booming tourism sector in a particular country will lead to several economic benefits. Despite these economic benefits, the tourism and hospitality industry should not disclaim climate change responsibilities such as rising sea levels, desertification, deforestation, or snow and ice melting. Particularly in the tourism sector, hotels contribute immensely to global warming through high energy and water consumption. Although the hotel industry has been initiating and promoting green concepts to contribute to environmental protection, consumers' demands are still uninspiring. Fewer preferences of green hotels by consumers has turn the investment in green hotels into a risky investment. In the hotel industry, consumers' attitudes and intentions towards green hotels have not been fully understood. Therefore, marketers are facing difficulties in attracting tourists to choose green premise. Besides, environmentally concerned consumers are temporarily fluctuating their preferences when choosing green hotels. Therefore, this study aims to examine the effect of environmental knowledge, perceived environmental responsibility, altruism, green price sensitivity, green availability on tourists' attitudes to visit green hotels in Malaysia. It further examined the effect of tourists' attitudes, subjective norms, and perceived behavioral control on tourists' intention to visit green hotels in Malaysia. The study aimed to look at the mediating effect of tourists' attitudes on the relationship between environmental knowledge, perceived environmental responsibility, altruism, green hotel price sensitivity, green hotel availability, and behavioural intention to visit green hotels in Malaysia. The study used a quantitative research design and interviewed 393 international tourists in Malaysia using systematic random sampling. Descriptive analysis was done using SPSS, and inferential analysis was conducted using SmartPLS software. The study found that environmental knowledge, perceived environmental responsibility, altruism, and green price sensitivity significantly influence attitude. It also found that environmental knowledge, altruism, green price sensitivity, green availability, attitude, perceived behavioral control, and subjective norm has a significant influence on intention. For mediating effects, attitude mediates the relationship between environmental knowledge, perceived environmental responsibility, altruism, green price sensitivity, and intention. This study speculates strong practical and theoretical contributions by highlighting the consumers' attitude and behavioural intention, along with the mediating effects concerning green practices in the hotel industry.